A STUDY ON JOB STRESS IN EVENT MANAGEMENT ORGANIZATIONS WITH REFERENCE TO THRISSUR DISTRICT, KERALA - S. Lakshmi and N. Somasundaram
In the present scenario, Event Management industry is one among the fastest growing industries in India. The Level of stress event managers and their employees face is high while compared to other industries; hence people at event management organizations and their job stress is chosen for this study. Every job has targets and employees become stressful in achieving their targets as well as when they are not able to achieve their targets. The main aim of this article is to highlight the level of stress faced by event managers and employees in Thrissur district. Total population of 10 event managers is selected for the present study by census method and 20 employees to represent these ten organizations by judgement sampling.